Macroprudential institutions in Europe - what are the blind spots? - Zeynep Mualla Nettekoven (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2020)
After the Great Financial Crisis of 2007-2008, macroprudential policy has increasingly become the mainstream. New institutions and regulations were introduced for macroprudential supervision in the EU Member States as well as at the supranational level. This leads us to the research question: what are the blind spots of this new macroprudential institutional design in the EU? This question gained even more in substance due to the repercussions of Covid-19 pandemic. Based on desk research and talks with experts, we group the blind spots into three categories: shadow banking system, institutional power hierarchies, and monetary and macroprudential policy interactions. In this paper, we discuss these blind spots and some policy recommendations for a functional macroprudential institutional design.
Keywords: E52; E58; G28; 330; macroprudential policy; institutions; Great Financial Crisis; shadow banking system